Clinical Profile and Management Patterns of Ectopic Pregnancy in a Tertiary Care Hospital in Bangladesh: A Cross-sectional Study (Bangladesh Journal of Medical Science, 2026)
Background Ectopic pregnancy remains a major cause of maternal morbidity and mortality in developing countries, often due to delayed diagnosis and late presentation. Objective To assess the patient profile, clinical presentation, and management of ectopic pregnancy cases in a tertiary care hospital. Methods This cross-sectional study was conducted at Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), Dhaka, from July 2012 to January 2013. All admitted patients with confirmed ectopic pregnancy were included. Data on age, parity, risk factors, clinical features, and management were collected using a structured checklist and analysed descriptively. Results The incidence was 10.16 per 1,000 pregnancies. Most patients were aged 26–30 years (40%). Previous abortion (28%) and pelvic infection (18%) were common risk factors. Abdominal pain was present in all cases, and 56% presented in shock. Most pregnancies were tubal (98%), mainly ampullary. Surgical management was predominant, with unilateral salpingectomy performed in 48% of cases 22. Conclusion Late presentation was common and often associated with complications. Early diagnosis, improved access to care, and greater reproductive health awareness are essential for improving outcomes.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 758-763